A Comparative Study Of Blockchain Algorithms For Non-Fungible Token - Woo, Jan Yin (2023)
In terms of performance, scalability, and latency, NFTs are a crucial implementation for humans no matter in cryptocurrency or digital asset ownership protection. However, there are some concerns for the community to consider before using NFTs technology universalness. The most important issue that is compulsory to overcome is the performance of blockchain algorithms in NFTs and the effect of scalability in each blockchain algorithm. Since a blockchain system is highly dependent on the protocols, a low-performance problem might be experienced. Other than that, a blockchain system might not be able to process if blocks are produced too fast. Therefore, this research will be a breakthrough of NFTs which could evaluate the performance of blockchain algorithms and determine the most suitable algorithms that may apply to NFTs. The proposed algorithms will be evaluated in terms of performance, scalability, and latency. In this research, there will be some selected algorithms, which is Proof-of-Work and Proof-of-Stakes from open resource and modified to the suitable testing criteria to evaluate valid and sufficient data for data visualization. All data will be done in chart view to make all comparative more obvious. From the result, one of the most suitable algorithms will be selected which is Proof-of-Stakes and the reasons are justified as in better performance, good scalability, and less latency. Therefore, this research will be on a testing for algorithms and determine the best algorithms that need to apply in NFTs.